An 11-Year Retrospective Research Study of the Predictive Factors of Peri-Implantitis and Implant Failure: Analytic-Multicentric Study of 1279 Implants in Peru - Frank Mayta-Tovalino; Yens Mendoza-Martiarena; Percy Romero-Tapia; María Álvarez-Paucar; Luis Gálvez-Calla; Juan Calderón-Sánchez; Rodolfo Bolaños-Cardenas; Antonio Diaz-Sarabia (Hindawi Limited, 2019)
Aim. To analyze the risk factors by logistic regression and perform the analysis of the survival rate of osseointegrated dental implants placed in public and private institutions. Methods. An analytic-multicentric study was carried out, where 1279 dental implants that were placed by specialists from January 2006 to October 2017 in public and private institutions (UPCH-SI, HCFAP, CMNAVAL, UPCH-SM, and UPSJB) were evaluated. The variables sex (X1), location (X2), hypertension (X3), antibiotic prophylaxis (X4), diabetes (X5), osteoporosis (X6), bisphosphonates (X7), history of periodontitis (X8), hypercholesterolemia (X9), bone quality (X10), bone quantity (X11), design (X12), smoker (X13), connection (X14), edentulism type (X15), staging (X16), 3D guided surgery (X17), load (X18), bone graft (X19), peri-implantitis (X20), mucositis (X21), and GBR (X22) were collected and analyzed by the Kaplan-Meier survival analysis. The logit analysis was performed among all the variables to choose the best statistical model that explains the true risk factors. The analysis was performed by multivariate logistic regression and the Kaplan-Meier test, at a level of statistical significance of p<0.05. Results. It was found that the failure rate of the 1279 implants evaluated was 17.98% corresponding to only 23 implants lost as they have good longevity over time. When establishing the best multivariate logistic regression model, it was found that the variables that remained stable in relation to their statistically significant value and more stable confidence intervals were age, osteoporosis, bisphosphonates, history of periodontitis, bone quality, bone graft, connection, number of implants, GBR (guided bone regeneration), and follow-up. Conclusions. Dental implants placed by specialists in public and private institutions had a failure rate similar to that in studies previously published in other countries.